The Community Housing Plan: The Role Of Capacity In Canadian On-Reserve Housing Policy - Kristen Harder (10855233) (2021)
On-Reserve Housing Policy is failing First Nation communities across Canada as it appears unable to meet the complex housing needs of First Nations people, or effectively manage the operation of housing systems on reserve. This paper explores whether a relationship exists between the ability of First Nations to develop and implement a Community Housing Plan (CHP) and capacity development on-reserve. It does this by questioning whether on-reserve housing policy has created the appropriate administrative, financial and governance capacity to support the successful implementation of Community Housing Plans onreserve. The research uses qualitative methodology, reviewing literature and seven reports that explore Indigenous history in Canada and Canadian On-Reserve Housing Policy. The findings contemplate the wider implications of On-Reserve Housing Policy when First Nation capacity is not supported by the Federal Government, and the role of planning in the decolonization of Indigenous housing and policy.